An outbreak of haemonchosis associated with anthelmintic resistance on a sheep farm in Kenya - Waruiru, R M (The Indian Journal of Animal Sciences, 2012)
An outbreak of haemonchosis associated with anthelmintic resistance was recorded in a flock of 150 Dorper sheep, ClosantelÂ (CLO) @ 5 mg kg -1 against Haemonchus contortus while fenbendazole (FBZ) and albendazole (ALB) reduced faecal egg counts by 27.5 and 38.0%,Â respectively. Levamisole (LEV) showed an efficacy of 92.3%. At double the recommended dose (10 mg kg -1 ), percentage reduction in faecal egg counts of sheep treated with FBZ and ALB varied between 69.9 and 75.7% and worm countsbetween 38.3 and 42.0%, respectively, confirming Haemonchus contortus resistance to these anthelmintics. These data indicatethat worm control strategies based on CLO or IVM could provide effective control of benzimidazole-resistant strains of H.contortus Kenyan farms.